2021
DOI: 10.26817/16925777.1001
|View full text |Cite
|
Sign up to set email alerts
|

Using Digital Formative Assessment to Evaluate EFL Learners’ English Speaking Skills

Abstract: As it is known formative assessment focuses on both the learning process and learner's performance. In this study digital formative assessment and traditional speaking tests were utilized comparatively to evaluate 52 upper-intermediate EFL learners' English language speaking skills. The study was designed as a mixed-method. The quantitative data were collected via achievement tests which had been administered both in traditional speaking tests and digital formative tests. The qualitative findings were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…Students stated, "I felt less nervous because I do not see the audiences in real life." This finding is in line with a similar finding by Köroğlu (2021) who found that students are able to express their ideas openly and clearly in online speaking assessments which is not possible in traditional speaking assessments due to stress and pressure. On the other hand, the current study also showed that students felt neutral about whether the grading systems of online assessment were fair and reliable.…”
Section: Discussionsupporting
confidence: 92%
“…Students stated, "I felt less nervous because I do not see the audiences in real life." This finding is in line with a similar finding by Köroğlu (2021) who found that students are able to express their ideas openly and clearly in online speaking assessments which is not possible in traditional speaking assessments due to stress and pressure. On the other hand, the current study also showed that students felt neutral about whether the grading systems of online assessment were fair and reliable.…”
Section: Discussionsupporting
confidence: 92%
“…Also, teachers' strategy of including recommendations with error corrections seems to positively affect learners' pronunciation since the audio and video resources advised by teachers to reinforce certain aspects of pronunciation are well-received by learners. Similar studies have demonstrated the positive effect of feedback throughout digital resources; Merry, et al (2008) proved that learners perceived audio file feedback more meaningful than written feedback; also, Köroğlu (2021) demonstrated that digital formative assessment further fluency and accuracy on learners.…”
mentioning
confidence: 64%
“…It can help students improve their learning and to know their strengths and weaknesses to achieve the target learning (Widiastuti, 2021). Likewise, formative assessment assists students in learning by allowing them to assess their work based on their learning progress -feedback for various types of teacher-made tests and performance assignments such as student portfolios (Koroglu, 2021). Previous studies have identified the formative assessment method as an effective system for remediating deficient learners by offering active feedback and supporting learning materials during guidance to improve student's learning outcomes (Fatahhela Dewi et al, 2020;Karaman, 2021;Tapingkae et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In the context of speaking, the teachers evaluate the students based on formative assessment criteria. Based on previous discussions, formative assessment provides many benefits to students in measuring their speaking test (Gautami & Santosa, 2021;Koroglu, 2021;Widiastuti, 2021). However, many teachers implement traditional assessments to assess students' speaking skills.…”
Section: Introductionmentioning
confidence: 99%